Associations of Visceral, Subcutaneous, Epicardial, and Liver Fat with Metabolic Disorders up to 14 Years After Weight Loss Surgery - Hunt, Steven C. (Metab Syndr Relat Disord, 2021)
Background: Bariatric surgery leads to long-term remission and reduced incidence of diabetes, hypertension, and dyslipidemia. Short-term studies suggest reduction in specific fat depots may be more predictive of health improvement than reduced body mass index (BMI). Visceral, subcutaneous, epicardial, and liver fat, measured 11 years after bariatric surgery, were associated with long-term remission and incidence of diabetes, dyslipidemia, and hypertension. Methods: Fat depots an average of 11 (maximum 14) years after surgery were quantified by noncontrast computed tomography in subjects who did (N = 261; 86% gastric bypass) or did not (N = 243) have bariatric surgery. Multiple regression related fat depots to disease endpoints with and without adjustment for change in BMI and surgical status. Results: Visceral fat was 42% lower, subcutaneous fat 20% lower, epicardial fat 30% lower, and liver-to-spleen density ratio 9% higher at follow-up in the bariatric surgery group compared with the nonsurgery group (all P < 0.01). Higher visceral fat at follow-up exam was significantly associated with reduced remission and increased incidence of diabetes, hypertension, and dyslipidemia. Subcutaneous fat was not associated with disease. The liver-to-spleen ratio was associated with the remission and incidence of hypertriglyceridemia and not with other fat depots. Epicardial fat was related to incidence of elevated low-density lipoprotein cholesterol and low high-density lipoprotein cholesterol. Conclusions: Whether or not a patient shows greater long-term diabetes, dyslipidemia, or hypertension remission or incidence after bariatric surgery appears dependent on the amount of fat within specific fat depots measured at follow-up. Furthermore, associations of the three disease endpoints with different fat depots suggest varied fat depot pathology.